Handbook of solid state diffusion. Volume 1, - Paul, Aloke; Divinski, S. V. (Elsevier, 2017)
"Handbook of Solid State Diffusion, Volume 1: Diffusion Fundamentals and Techniques covers the basic fundamentals, techniques, applications, and latest developments in the area of solid-state diffusion, offering a pedagogical understanding for students, academicians, and development engineers. Both experimental techniques and computational methods find equal importance in the first of this two-volume set. Volume 1 covers the fundamentals and techniques of solid-state diffusion, beginning with a comprehensive discussion of defects, then different analyzing methods, and finally concluding with an exploration of the different types of modeling techniques. Presents a handbook with a short mathematical background and detailed examples of concrete applications of the sophisticated methods of analysis ; Enables readers to learn the basic concepts of experimental approaches and the computational methods involved in solid-state diffusion ; Covers bulk, thin film, and nanomaterials Introduces the problems and analysis in important materials systems in various applications ; Collates contributions from academic and industrial problems from leading scientists involved in developing key concepts across the globe"--Provided by publisher.